The Effect of Adding ZnO Nanoparticles to Radiator Coolant on Heat Transfer Performance in Motor Vehicle Cooling Systems - Elka Faizal; Sugeng Hadi Susilo (PT. ELSHAD TECHNOLOGY INDONESIA, 2025)
This study investigates the impact of adding Zinc Oxide (ZnO) nanoparticles to radiator coolant to enhance the heat transfer performance of automotive cooling systems. The research explores the optimal concentration of ZnO nanofluids and examines operational conditions such as flow rates (7-11 lpm) and fluid temperatures (60°C, 70°C, and 80°C) to determine their effect on heat transfer performance. The results demonstrate that ZnO nanoparticles significantly improve the heat transfer coefficient, with the highest performance observed at a concentration of 0.35% ZnO and a temperature of 70°C. The optimal combination of flow rate (10 lpm) and temperature (70°C) resulted in a 62.86% increase in heat transfer compared to conventional coolant. This study provides valuable insights into selecting the optimal nanofluid concentration and operational conditions for improving vehicle radiator performance.